The Oral Health Status, the Physical Status and the Independence for Brushing, Denture Wearing, Mouth Rinsing of Elderly Residents at a Special Nursing Home for the Elderly - Urasaki, Hiroyuki; Soyama, Yoshiyuki; Hirata, Yonesato; Nakagawa, Hideaki (Ronen Shika Igaku, 2003)
The aim of this study was to evaluate the oral health status, the degree of independence for brushing, denture wearing and mouth rinsing and the physical status of the elderly residents at a special nursing home for the elderly, and to clarify the relations between these three factors. The subjects were 72 residents (mean age 84 years) at a special nursing home for the elderly. Two general dental practitioners performed an oral examination and a nursing home helper investigated the status of life, the denture, oral by giene and systemic health status by means of a questionnaire. Cerebro-vascular disease was the most prevalent disease, 9 residents had a history of pneumonia and the“Kizami” meal was the most common diet. Sixty-one % of the residents had dentures. As for the BDR index, over half of the subjects were independent in tooth brushing, but less than half were really capable. Dementia patients needed significantly more help with tooth brushing and with insertion, removal and of rinsing of dentures. Subjects who took normal meals were independent on the BDR index. This showed the importance of normal meals.